Treatment of hepatitis C in HCV mono-infected and in HIV-HCV co-infected patients: an open-labelled comparison study (Swiss Medical Weekly, 2010)
Background/aims: Treatment of chronic HCV infection has become a priority in HIV+ patients, given the faster progression to end-stage liver disease. The primary endpoint of this study was to evaluate and compare antiviral efficacy of Peginterferon alpha 2a plus ribavirin in HIV-HCV co-infected and HCV mono-infected patients, and to examine whether 6 months of therapy would have the same efficacy in HIV patients with favourable genotypes 2 and 3 as in mono-infected patients, to minimise HCV-therapy-related toxicities. Secondary endpoints were to evaluate predictors of sustained virological response (SVR) and frequency of side-effects. Methods: Patients with genotypes 1 and 4 were treated for 48 weeks with Pegasys® 180 µg/week plus Copegus® 1000–1200 mg/day according to body weight; patients with genotypes 2 and 3 for 24 weeks with Pegasys® 180 µg/week plus Copegus® 800 mg/day. Results: 132 patients were enrolled in the study: 85 HCV mono-infected (38: genotypes 1 and 4; 47: genotypes 2 and 3), 47 HIV-HCV co-infected patients (23: genotypes 1 and 4; 24: genotypes 2 and 3). In an intention-to-treat analysis, SVR for genotypes 1 and 4 was observed in 58% of HCV mono-infected and in 13% of HIV-HCV co-infected patients (P = 0.001). For genotypes 2 and 3, SVR was observed in 70% of HCV mono-infected and in 67% of HIV-HCV co-infected patients (P = 0.973). Undetectable HCV-RNA at week 4 had a positive predictive value for SVR for mono-infected patients with genotypes 1 and 4 of 0.78 (95% CI: 0.54–0.93) and of 0.81 (95% CI: 0.64–0.92) for genotypes 2 and 3. For co-infected patients with genotypes 2 and 3, the positive predictive value of SVR of undetectable HCV-RNA at week 4 was 0.76 (95%CI, 0.50–0.93). Study not completed by 22 patients (36%): genotypes 1 and 4 and by 12 patients (17%): genotypes 2 and 3. Conclusion: Genotypes 2 or 3 predict the likelihood of SVR in HCV mono-infected and in HIV-HCV co-infected patients. A 6-month treatment with Peginterferon alpha 2a plus ribavirin has the same efficacy in HIV-HCV co-infected patients with genotypes 2 and 3 as in mono-infected patients. HCV-RNA negativity at 4 weeks has a positive predictive value for SVR. Aggressive treatment of adverse effects to avoid dose reduction, consent withdrawal or drop-out is crucial to increase the rate of SVR, especially when duration of treatment is 48 weeks. Sixty-one percent of HIV-HCV co-infected patients with genotypes 1 and 4 did not complete the study against 4% with genotypes 2 and 3.